2017
DOI: 10.26493/2335-4194.10.115-128
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Positioning of Self and Social Identities as Antecedents in Cultural-Experiential Tourism

Abstract: Museums are often regarded as a cultural destination, however they stand distinct from other purveyors of culture in that they consciously attempt at a less pronounced social and cognitive dissonance among the audience it covets. In their strife for continuity as an overarching goal, museums by necessity have moved away from being torchbearers of heritage and interpretive centers thereof, to being experiential centers and thus facing challenges associated with a duality of roles. Conscious democratization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…However, research evidence claims that this theory falls short of more granularly examining individual motivations from an identity-seeking perspective (Nath & Saha, 2017). Therefore, this research contributes to knowledge by investigating/classifying the extent to which escape is driven by individual personal and social identity motivations.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, research evidence claims that this theory falls short of more granularly examining individual motivations from an identity-seeking perspective (Nath & Saha, 2017). Therefore, this research contributes to knowledge by investigating/classifying the extent to which escape is driven by individual personal and social identity motivations.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 97%
“…For instance, Laing and Frost (2017) found that Italy's destination factors-food, wine, art, and lifestyle-helped to change people's identity because they were seen by respondents as an 'exotic other'. Nath and Saha (2017) suggest that museums as destination factors are motivation determinants in cultural experience tourism in terms of identity-seeking and identity-projection behaviour. These pull motivating factors have differential effects on an individual's identity needs, and together, they can influence an individual's motivation to escape for travel.…”
Section: Self-categorisation Theory and Tourist Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…We, however, consider these to belong to social identity. In our view, self-identity is a quest for retaining a consistent thread in one's life, by which one interprets and anchors the self (Nath & Saha, 2017). Conner and Armitage (1998) viewed self-identity to be distinct from a person's moral values.…”
Section: Self-identitymentioning
confidence: 99%
“…As Gleason (1983) stated about self-identity, "Its very obviousness seems to defy elucidation!" Taking a psychological approach, self-identity would be likened to what remains consistent through a person's phases of existence, a continuity of his personality, a matter of retaining a "sameness" (Nath & Saha, 2017). Gleason (1983), while equating identity to an integrity of the self, vacillated in his discussion of self-identity between the sense mentioned above, and other forms of identity such as political, ethnic, and others.…”
Section: Self-identitymentioning
confidence: 99%